COMMUNICATION AUDIT OF THE BINJAI CITY NATIONAL NARCOTICS AGENCY (BNN) IN SOCIALIZING THE DANGERS OF DRUGS - Dian Permata; Lies Utami Efni Safitri (Journal Analytica Islamica, 2026)
This study aims to analyze the communication audit of the National Narcotics Agency (BNN) of Binjai City in implementing socialization of the dangers of drug abuse, with a focus on the message planning process, the use of communication media, audience response, and obstacles to program evaluation. This study used a descriptive qualitative approach with data collection techniques through in-depth interviews with three informants from the BNN Binjai City public relations department, observation of socialization activities, and documentation. The results showed that the socialization activities were carried out informatively and persuasively through direct counseling, interactive discussions, visual media, and the use of social media. The socialization messages were also tailored to the characteristics of the audience, thus encouraging participation and a positive response from the community. However, the communication audit showed that the evaluation aspect remains a major weakness. Program evaluation is still general, focusing on the number of participants and activity participation, and is not supported by measurable indicators, standardized evaluation instruments, or systematic management of community feedback. This finding confirms that the effectiveness of socialization of the dangers of drugs is determined not only by the success of message delivery, but also by the organization's ability to evaluate the impact of communication on an ongoing basis. This study recommends strengthening data-driven evaluation systems, developing measurable success indicators, and optimizing communication technology to increase the effectiveness of the Binjai City National Narcotics Agency (BNN) outreach program.